Impact of Salinity on the Gastrointestinal Bacterial Community of Theodoxus fluviatilis - Kivistik, Carmen; Knobloch, Jan; Käiro, Kairi; Tammert, Helen; Kisand, Veljo; Hildebrandt, Jan-Peter; Herlemann, Daniel P. R. (Frontiers in Microbiology, 2020)
Differences in salinity are boundaries that act as barriers for the dispersal of most aquatic organisms. This creates distinctive biota in freshwater and brackish water (mesohaline) environments. To test how saline boundaries influence the diversity and composition of host-associated microbiota, we analyzed the microbiome within the digestive tract of Theodoxus fluviatilis, an organism able to cross the freshwater and mesohaline boundary. Alpha-diversity measures of the microbiome in freshwater and brackish water were not significantly different. However, the composition of the bacterial community within freshwater T. fluviatilis differed significantly compared with mesohaline T. fluviatilis and typical bacteria could be determined for the freshwater and the mesohaline digestive tract microbiome. An artificial increase in salinity surrounding these freshwater snails resulted in a strong change in the bacterial community and typical marine bacteria became more pronounced in the digestive tract microbiome of freshwater T. fluviatilis. However, the composition of the digestive tract microbiome in freshwater snails did not converge to that found within mesohaline snails. Within mesohaline snails no cardinal change was found after either an increase or decrease in salinity. In all samples, Pseudomonas, Pirellula, Flavobacterium, Limnohabitans and Acinetobacter were among the most abundant bacteria. These bacterial genera were largely unaffected by changes in environmental conditions. As permanent residents in T. fluviatilis they may support the digestion of the algal food in the digestive tract. Our results show that freshwater and mesohaline water host-associated microbiomes respond differently to changes in salinity. Therefore, the salinization of coastal freshwater environments due to a rise in sea level can influence the gut microbiome and its functions with currently unknown consequences for e.g. nutritional physiology of the host.